THE EFFECT OF SERVICE QUALITY, PROMOTION, AND CUSTOMER EXPERIENCE ON CUSTOMER SATISFACTION AT BRK SYARIAH IN UJUNGBATU, ROKAN HULU - Mei Denissa Putri; Syahdanur (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to determine and analyze the effect of service quality, promotion, and customer experience on customer satisfaction at BRK Syariah in Ujungbatu, Rokan Hulu Regency. Increasing competition in the banking industry requires banks to improve service quality, implement effective promotional strategies, and create positive customer experiences in order to enhance customer satisfaction. This research used a quantitative method with a descriptive approach and multiple linear regression analysis. The population in this study consisted of customers of BRK Syariah in Ujungbatu Rohul, with a sample of 96 respondents determined using the Lemeshow formula and selected through a purposive sampling technique. Data were collected through questionnaires using a Likert scale. Data analysis was conducted using the SPSS program, including validity tests, reliability tests, classical assumption tests, and hypothesis testing. The results showed that partially service quality, promotion, and customer experience have a significant effect on customer satisfaction. Simultaneously, these three variables also have a significant effect on customer satisfaction at BRK Syariah in Ujungbatu Rohul. The findings indicate that better service quality, effective promotion, and positive customer experience can increase the level of customer satisfaction. Therefore, BRK Syariah is expected to continuously improve service quality.